2020
DOI: 10.1152/japplphysiol.00315.2019
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular lean mass is lower in late compared with early perimenopausal women: potential role of FSH

Abstract: OBJECTIVE The age‐related decline in skeletal muscle mass (i.e. sarcopenia) and bone mineral density (BMD; i.e. low bone mass, osteoporosis) contribute to physical disability in older women. Although menopause‐related loss of BMD is well documented, whether menopause influences muscle mass and sarcopenia is unclear. We determined the extent to which appendicular lean mass (ALM) and BMD differ across the stages of menopause in healthy women. METHODS 145 women (aged 30–70 years) classified as premenopausal (Pre;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
2
26
1
Order By: Relevance
“…Our results indeed showed a steep decline in FSH levels at 6-month after Degarelix administration, confirming published data [ 29 ]. A recent Korean study has shown that ALMI measured across menopause stages in a series of women was inversely correlated to FSH but not to estradiol [ 30 ]. These data suggest that FSH may negatively influence muscle mass and favor sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indeed showed a steep decline in FSH levels at 6-month after Degarelix administration, confirming published data [ 29 ]. A recent Korean study has shown that ALMI measured across menopause stages in a series of women was inversely correlated to FSH but not to estradiol [ 30 ]. These data suggest that FSH may negatively influence muscle mass and favor sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a pathogenic role of FSH with regard to this unwanted physical and metabolic condition. So the greater reduction in serum FSH after LHRH antagonists compared to agonists [ 29 , 30 ] provides a possible mechanism of reduction in the risk of sarcopenic obesity associated with the administration of the former drugs as compared to the latter. These data, if confirmed, are relevant in view of the increasing impact of obesity and sarcopenia on the CVD risk in long surviving patients with PCa.…”
Section: Discussionmentioning
confidence: 99%
“…All assays were performed by the Colorado Clinical and Translational Sciences Institute (CCTSI) Clinical and Translational Research Center (CTRC) Core laboratory, which is CAP-and CLIA-accredited. The intra-and inter-assay coefficients of variation have been described previously [24]. The coefficient of variation (CV, 95% CI) for each hormone are as follows: intra-assay CV: estradiol, 4.3%; estrone, 11.5%; FSH, 1.8%; progesterone, 4.4%; testosterone, 2.1%; IL6, 7.8%; and inter-assay CV: estradiol, 8.2%; estrone, 19.8%; FSH, 3.8%; progesterone, 7.9%; testosterone, 5.1%; IL6, 11%.…”
Section: Sex Hormones and Inflammatory Markermentioning
confidence: 99%
“…However, less is known about whether skeletal muscle mass and the prevalence of sarcopenia differ between the menopausal stages. Using a cross-sectional study ( 5 ), we recently determined that perimenopausal transition is a vulnerable period for the loss of muscle mass. One hundred forty four healthy women (aged 30–70 yr) were classified as premenopausal (n=30), early (n=31) and late perimenopausal (n=30), and early (n=26) and late postmenopausal (n=27).…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%
“…Appendicular lean mass (ALM) index, calculated by ALM adjusted by the square of height, was assessed using dual-energy x-ray absorptiometry ( 5 ).…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%